Hypertension and Its Associated Risk Factors in the Kingdom of Saudi Arabia, 2013: A National Survey - Charbel El Bcheraoui; Ziad A. Memish; Marwa Tuffaha; Farah Daoud; Margaret Robinson; Sara Jaber; Sarah Mikhitarian; Mohammad Al Saeedi; Mohammad A. AlMazroa; Ali H. Mokdad; Abdullah A. Al Rabeeah (International Journal of Hypertension)
Current data on hypertension in the Kingdom of Saudi Arabia are lacking. We conducted a national survey to inform decision-makers on the current magnitude of the epidemic. We measured systolic and diastolic blood pressure of 10,735 Saudis aged 15 years or older and interviewed them through a national multistage survey. We used multivariate logistic regressions to describe sociodemographic characteristics and risk factors of hypertensive, borderline hypertensive, and undiagnosed hypertensive Saudis. We found that 15.2% and 40.6% of Saudis were hypertensive or borderline hypertensive, respectively. Risk of hypertension increased among men, with age, obesity, diabetes, and hypercholesterolemia. 57.8% of hypertensive Saudis were undiagnosed. These were more likely to be male, older, and diagnosed with diabetes. Among participants diagnosed with hypertension, 78.9% reported taking medication for their condition. About 45% of participants on medication for hypertension had their blood pressure controlled. The prevalence of hypertension and borderline hypertension is very high in Saudi Arabia. Moreover, control of hypertension is poor. With the majority of hypertensive Saudis being unaware of their condition, a national plan is needed to increase utilization of freely available screening, preventive, and medical services.